Serum Lactate Albumin Ratio as a Predictor of Mortality in Severe Sepsis and Septic Shock at Tribhuwan University Teaching Hospital, Kathmandu - Thapa, Sameer; Prasad, PN; Shakya, YM (Birat Journal of Health Sciences, 2017)
IntroductionSevere sepsis and septic shock, is a common cause of emergency room admission and is associated with high morbidity and mortality worldwide. This study inspects the prediction of mortality in severe sepsis and septic shock with increased lactate/albumin ratio.Objective The objective of the study was to predict the serum lactate albumin ratio as an indicator of mortality in severe sepsis and septic shock.MethodologyIt was a hospital based cross sectional study done at Tribhuvan University Teaching Hospital, Kathmandu from November 2015 to October 2016. The consent was taken from patients. Acute Physiology and Chronic Health Evaluation II score, serum lactate and serum albumin levels on first day of arrival in emergency room were calculated. Patients were classified as severe sepsis and septic shock and treated according to Surviving Sepsis Campaign 2012 guideline. The patient were follow up at 28 day, The associations of 28-day outcome with Acute Physiology and Chronic Health Evaluation II score, serum lactate value, serum albumin value and serum lactate albumin ratio value were derived.ResultsOut of total 240 severe sepsis and septic shock patients it is found that increased serum lactate/albumin ratio was an independent predictor of the mortality with cut off value of 0.07. Furthermore serum lactate albumin ratio shows strong correlation with APACHE 2 score in predicting mortality in severe sepsis and septic shock.ConclusionIncreased lactate/albumin ratio predicts mortality in patients with severe sepsis and septic shock.  Birat Journal of Health Sciences  Vol.2/No.1/Issue 2/ Jan - April 2017, Page: 191-195